2000
DOI: 10.1177/096368970000900612
|View full text |Cite
|
Sign up to set email alerts
|

Human Pancreatic Islets Transfected to Produce an Inhibitor of TNF are Protected against Destruction by Human Leukocytes

Abstract: The objective of this study was to determine whether transfection of human islets with an adenovirus construct encoding an inhibitor of tumor necrosis factor (TNFi) was effective at limiting damage to beta cells induced by human peripheral blood leukocytes (huPBL). Human islets transfected with TNFi or control islets were transplanted under the kidney capsule of NOD-scid mice. After a 15-day engraftment period, half of the mice received injections of activated huPBL and half received buffer injections. Islet g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…42 Furthermore, reduction of glucose concentration back to basal level has resulted in reduction in insulin response to basal level in all cases, indicating that the islets do remain dynamically responsive to glucose concentration. Our results for the in vitro islet function test are in good agreement with the work of Dobson et al,26 who demonstrated that the transfection of human islets with the adenovirus did not affect graft function in NOD-SCID mice recipients, as human insulin secretion from the transfected and non-transfected grafts did not differ. This is also consistent with the results reported by others showing that transfection of islets with adenoviral vectors does not inhibit islet graft function in allograft or xenograft models.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…42 Furthermore, reduction of glucose concentration back to basal level has resulted in reduction in insulin response to basal level in all cases, indicating that the islets do remain dynamically responsive to glucose concentration. Our results for the in vitro islet function test are in good agreement with the work of Dobson et al,26 who demonstrated that the transfection of human islets with the adenovirus did not affect graft function in NOD-SCID mice recipients, as human insulin secretion from the transfected and non-transfected grafts did not differ. This is also consistent with the results reported by others showing that transfection of islets with adenoviral vectors does not inhibit islet graft function in allograft or xenograft models.…”
Section: Discussionsupporting
confidence: 91%
“…26 These mice lack mature T and B lymphocytes and thus cannot mount adaptive immune responses to reject xenografts of human islets. In this model, islet viability is assessed by measuring human Cpeptide and insulin levels in response to glucose challenge.…”
Section: Islet Isolation and Culturementioning
confidence: 99%
“…The low frequency of islet grafting is dependent on poor islet recovery from donors [4] and early islet loss during the first hours after grafting [5,6], termed primary graft nonfunction. Islet transplantation exposes cells to a variety of stressful stimuli, notably proinflammatory cytokines that encourage beta cell death and lead to early graft failure [7][8][9]. The reduction in islet mass immediately after transplantation implicates beta cell death by apoptosis and the prerecruitment of intracellular death-signalling pathways [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Generalized immunosuppression using steroids (Corbett et al, 1993) Ex vivo gene therapy using IL-1 receptor antagonist (Gysemans et al, 2003) TNF-␣ Administration of soluble TNF-␣ receptor (Farney et al, 1993) Adv transfection of inhibitor of TNF-␣ (TNFi) (Dobson et al, 2000) …”
Section: Immune Modulation Andmentioning
confidence: 99%